KOMPARASI TEKNIK ABC/2 DAN ASISTEN ANALISIS VOLUMETRIK KOMPUTER PADA SUBDURAL HEMATOMA DENGAN PEMERIKSAAN CT SCAN DI RUMAH SAKIT SITI KHODIJAH MUHAMMADIYAH SEPANJANG - Rahmadhani, Vaiza Eka; Muslim Andala Putra; Laily Irfana (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2025)
Subdural Hematoma (SDH) is a common pathological condition characterized by venous bleeding in the subdural space between the dura mater and the arachnoid membrane. Computed tomography (CT) scan plays a crucial role in diagnosing SDH and assessing the severity of the hemorrhage by estimating the hematoma volume.  Various measurement techniques, including the ABC/2 formula and volumetric analysis, are used to determine SDH volume. This study aimed to compare the SDH volume results obtained from the ABC/2 technique and the volumetric technique using Philips Access CT V2.0 computer software. A cross-sectional study was conducted involving 30 patients diagnosed with SDH based on CT scan findings at Siti Khodijah Muhammadiyah Hospital, Sepanjang, Sidoarjo. Volume measurements were performed by a radiologist using the hospital’s radiology computer. The ABC/2 technique involved manual measurement using linear dimensions, while the volumetric technique utilized Philips Access CT V2.0 computer software to obtain three-dimensional volume estimates. Data were analyzed using the Wilcoxon signed-rank test to determine statistical differences between the two techniques. The analysis showed no significant difference between the volumes measured by the ABC/2 and the volumetric techniques (p = 0.382; p > 0.05). In conclusion, the ABC/2 technique remains a practical and time-efficient method for estimating SDH volume, especially in clinical settings where rapid assessment is required.